Insights from Adult Learning Theory: Enhancing Academicians' Mental Health and Well-being in a Research-Driven World - Singh, Monu; Kardam, Neha; Rahmatulla, Sahnaj; Laskar, Narghis Habiba; Bhattacharjee, Abhigyan (Journal of Management World, 2025)
This article intends to advance the understanding of how Adult Learning Theory (ALT) can serve the purpose of raising the mental health and well-being of professionals engaged in research-focused activities through the implementation of relevant and theoretically grounded targeting components that address their problems. As suggested by literature review findings, self-concept, experience and motivation are important components of ALT and serve as the building blocks for strategies used to cope with stress and promote resilience and better quality of life in the highly competitive environments. The findings suggest team work, communication, mindfulness, informal networking and other interactions as resources for improving mental health and building resilient communities. Practical applications involve introduction of programs based on ALT aimed at striking a balance between professional and family life, periodic monitoring and altering the approach taken in managing mental health. Although the parameters studied are not grounded in empirical evidence and do not take organizational culture into account, the study presents itself as a useful framework for institutions grappling with the thorny issue of mental health amongst academics. By alleviating stigma and encouraging flexibility, this work fills an important deficiency, providing new insights and solutions based on theories to enable better academic well-being.